'A Change of Heart': Racial Politics, Scientific Metaphor and Coverage of 1968 Interracial Heart Transplants in the African American Press. (26th May 2016) - Koretzky, Maya Overby
Abstract: This paper explores the African American response to an interracial heart transplant in 1968 through a close reading of the black newspaper press. This methodological approach provides a window into African American perceptions of physiological difference between the races, or lack thereof, as it pertained to both personal identity and race politics. Coverage of the first interracial heart transplant, which occurred in apartheid South Africa, was multifaceted. Newspapers lauded the transplant as evidence of physiological race equality while simultaneously mobilising the language of differing 'black' and 'white' hearts to critique racist politics through the metaphor of a 'change of heart'. While interracial transplant created the opportunity for such political commentary, its material reality—potential exploitation of black bodies for white gain—was increasingly a cause for concern, especially after a contentious heart transplant from a black to a white man in May 1968 in the American South.